Molecular Identification Of Human Papilloma Virus Genotypes In Patients With Cervical Cancer - Juan Carlos Piña Napal; Gustavo Crespo Campos; Rafael Fando Calzado; Yaimara Valdés Silva (Revista Cubana de Investigaciones Biomédicas, 2019)
Background: The principal cause of cervical cancer is human papillomavirus. In Camaguey population, molecular study about human papillomavirus does not exist. The Polimerase Chain Reaction is a molecular procedure often used for medical diagnostic; it allow to confirm the human papillomavirus DNA in the total DNA purified of cervical cancer patients sample.